Local knowledge and environmentality in legitimacy discourses on Irish peatlands regulation. (31st December 2016) - O'Riordan, Margaret; McDonagh, John; Mahon, Marie
Highlights: Local ecological and cultural subjectivities frequently run contrary to the aims of regulation. Top-down, non-communicative governance undermined trust and legitimacy. Post-colonial attitudes towards property rights and governance form barriers to regulation. Adaptive governance and the integration of local knowledge contributed significantly to positive attitudes on SAC conservation. Transformative change requires addressing inconsistencies and inequities underlying conservation policy. Abstract: In this paper Q Methodology and environmentality are utilized to dissect multi-subjectivities on local environmental knowledge underlying peatland conservation through the implementation of the EU Habitats Directive in Ireland. The results offer insights into the cultivation of moral responsibility for nature regulation and its legitimacy at ground level. Alignments and gaps between local cultural and ecological knowledge and the science and governance of peatlands are revealed across three discourses. Legitimacy of regulation of domestic turf cutting is found to be undermined by deeply-held postcolonial subjectivities on property rights and governance in addition to perceived government failure to regulate ongoing harvesting on non-SAC (Special Areas of Conservation) peatlands. The science-first and exclusionary approach adopted by conservation authorities in its approach to designation has served to undermine trust in the science underlying peatland regulation and in the national agency for nature conservation. Recent moves integrating bottom-up practices and local knowledge into relocation policy through adaptive governance reveal a more positive attitude to conservation management but also foster ambivalence towards the conservation potential of non-SAC peatlands. Overall, the research exposes how local environmental subjectivities respond to perceived inequities and inconsistencies in peatlands regulation.